(untitled) (The Review of Diabetic Studies, 2023)
The diverse actions of the incretin hormone glucagon-like peptide (GLP)-1 include insulinotropic, beta-cell preservative, cardioprotective and vasodilatory effects. This spectrum makes GLP-1 an appealing therapeutic option for patients with type 2 diabetes. However, its rapid metabolism by the enzyme dipeptidyl peptidase (DPP)-4 renders it impractical. Incretin-based analogues have been developed to extend endogenous GLP-1 action (GLP-1 receptor agonists) and to hamper its degradation (DPP-4 inhibitors). Evidence suggests that GLP-1 receptor agonists and DPP-4 inhibitors have different pharmacodynamic and pharmacokinetic effects. For example, GLP-1 receptor agonists deliver supraphysiologic levels of GLP-1 analogues designed to resist inactivation by DPP-4, whereas DPP-4 inhibition conserves native GLP-1 resulting in concentrations within the physiologic range. Furthermore, GLP-1 receptor agonists induce glucose-dependent insulin secretion, beta-cell protection, and other extraglycemic benefits such as weight loss and improvement in markers of cardiovascular risk. In contrast, DPP-4 inhibitors are weight neutral and have modest effects on glucose control. DPP-4 inhibition is dependent on the availability of endogenous GLP-1, which appears to be adversely affected by type 2 diabetes and its progression. Therefore, DPP-4 inhibitors may be better suited for patients with mild hyperglycemia without comorbidities. This review examines the present understanding of the pancreatic effects of endogenous GLP-1, and the extrapancreatic actions it exerts on human bodily systems. Also, it analyzes available preclinical and clinical data on incretin therapies with respect to glycemia, lipids, blood pressure, and weight.